Daily and Weekly Rehabilitation Delivery for Young Children With Gross Motor Delay: A Randomized Clinical Trial Protocol (the DRIVE Study). Issue 2 (April 2019) - Ferrante, Rachel; Hendershot, Sarah; Baranet, Kathy; Barbosa, Gardenia; Carey, Helen; Maitre, Nathalie; Lo, Warren; Pan, Jeff; Heathcock, Jill
Abstract : Purpose: The proposed project tests the principle that frequency of rehabilitation is an important regulator of therapeutic response in infants. Methods: We will randomize 75 infants with cerebral palsy, 6 to 24 months of age and/or Gross Motor Function Classification System levels III to V (higher severity), to determine the short-term and long-term effects of 3 dosing protocols consisting of an identical number of 2-hour sessions of the same motor learning-based therapy applied over a different total number of calendar weeks. Results and Conclusions: The results will inform clinicians, families, and scientists about dosing and will provide needed recommendations for frequency of rehabilitation to optimize motor function and development of young children with cerebral palsy. Abstract : The proposed project tests a hypothesis that frequency of rehabilitation is an important regulator of therapeutic response in infants and does not test the efficacy of a type of treatment.